Flood Risk on Hospital Utility and Mitigation Measures - Ain Yusoff, Noor; Shafii, Haryati; OMar, Roshartini (International Journal of Engineering and Technology, 2018)
Malaysia is geographically located outside of the Pacific fire circle that is free of any incidents and property destroyed by natural disaster such as hurricanes, earthquakes and volcanic eruptions. However, Malaysia is also vulnerable to natural disasters such as floods, landslides and haze. In Malaysia, flood is one of the most frequent catastrophic disasters that have caused major damage to property and loss of life. The floods in 2014 had a significant impact on the hospital, especially in Kelantan, Malaysia. Flooding of hospital result in interruption of utilities supplies such as water, electrical power, fuel and medical gas. This paper try to explore major and potential challenges faced by the operation of hospital specifically related to utilities supplies and reduce flood risk of the hospital utilities supplies through the best measures. From the discussion, the risk of floods especially on the supply utilities hospitals can be mitigated through the best identified measures as well as can maintain the daily hospital treatment of patients, particularly ill patients.Â